Plasticity constitutive routines for finite element analysis - Aristorenas, George V. (1987)
The classical elasto-static Finite Element analysis assumes that the continuum adopts a linear elastic response, irregardless of the magnitude of the applied loads or deformations. This assumption is valid for materials tested to behave elastically under normal service load conditions. This is no longer true in failure or fracture analysis since, at these conditions, the material would have exhibited some form of non-linearity in its response. In fact for some materials such as concrete and soil, a non-linear response may be encountered even during the early stages of loading. For such cases, a non-linear analytical tool is needed. This thesis therefore presents plasticity constitutive routines that can be integrated in a Finite Element Program. The Constitutive routines use the Tresca and Von Mises yield functions, two criteria experimentally verified to be valid for metals. Formulation is based upon an associated flow rule where the yield function is also the plastic potential at the same time.
The routines are used to analyze three problems: uniaxial compression of both an unconstrained and constrained cylindrical specimen, and a thick-walled cylinder subjected to internal pressure. Program listings of plasticity constitutive routines are also provided.
Thesis (M.S.)--University of the Philippines Diliman.
Typescript.
Keywords: Plasticity; Finite element method